استخدام الخوارزميات في بناء وتخزين حزمة محتوى تعليمي في مستودع كائن التعلم وفق معيارSCORM - كندة أبو قاسم; بلال شيحا; هناء سلمى (Tishreen University, 2019)
سعينا من خلال هذا البحث إلى استخدام الخوارزميات في بناء محتوى تعليمي(Content) خاضع لمعيار SCORM(Shareable Content Object Reference Model) ومن ثم تخزينه ضمن مستودع كائن التعلم(Learning Object Repository (LOR)). وقد شملت هذه العملية عدة خطوات وهي تحويل حزمة المحتوى(Content Package) المشكلة وفق معيار SCORM إلى تركيب يشبه شجرة ويدعى شجرة المحتوى ((CT)Content Tree) وذلك لتمثيل كل قطعة من المادة التعليمية بالاعتماد على مفهوم نموذج فضاء الحالة(Vector Space Model)، وعلى قانون TF×IDF(Term Frequency × Inverse Document Frequency)، وعلى مفهوم خوارزميات الأشجار، وذلك لتمثيل كل عقدة محتوى بشعاع مميزة يعبر عن معلومات هذه العقدة، ومن ثم تجميع عقد المحتوى في عناقيد باعتماد قانون قياس التشابه(similarity measure) بين كل عقدتين من عقد أشجار المحتوى ووفقاً لعتبة تشابه محددة وتم تعديل دقة العناقيد من خلال قياس التشابه للعناقيد الناتجة. This research uses algorithms for building SCORM compliant learning content, storing it within a learning object repository. This process includes many steps: transforming SCORM compliant content package into a composition similar to a tree called "Content Tree" for representing each part of learning material; depending on concept of vector space model; Term Frequency-Inverse Document Frequency (TF-IDF) weighting scheme; and concept of trees algorithms. The aim is to represent each content node by a feature vector that expresses information of this node and then gathers content nodes in clusters by adopting a similarity measure between every two nodes of tree content nodes according to a specific similarity threshold. The accuracy  of clusters has been adjusted through measuring the similarity of  resulted clusters.